Using of 199Tl-сhloride and 99mTc-MIBI in indications and differential diagnostics inflammatory and neoplastic processes of musculoskeletal system - A. P. Kourazhov; V. D. Zavadovskaya; O. Yu. Kilina; M. A. Zorkaltsev; Ye. L. Choinzonov; V. I. Chernov; Ye. M. Slonimskaya; A. V. Bogoutdinova; I. I. Anisenya; A. A. Titskaya; R. V. Zelchan; I. G. Frolova; et al. (Бюллетень сибирской медицины)
Potentialities of 199Tl-chloride and 99mTc-MIBI scintigraphy in diagnostics of musculoskeletal system inflammatory and tumor processes were assessed. Nonspecific indications of inflammations and tumors were obtained in 92.6 и 98.5% respectively. Accuracy 199Tl-chloride and 99mTc-MIBI scintigraphy in diagnostics inflammations were 83.7 and 73.2% respectively, tumors were 88.8 и 75.6% respectively. These markers both are available for indications, and 199Tl-chloride for differentiations of them.